2017
DOI: 10.1044/persp2.sig1.203
|View full text |Cite
|
Sign up to set email alerts
|

Language of Intervention in Bilingual Children With Autism Spectrum Disorders

Abstract: Selecting the appropriate language of intervention for bilingual children with language impairment is difficult, especially for bilingual children with autism spectrum disorders (ASD) as their families are often encouraged by professionals to select one language only for communication. The limited evidence supports the use of bilingual language interventions when working with bilingual children with ASD. The current study sought to expand this limited work by presenting preliminary data of the effects of a bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…Thordardottir, Weismer, and Smith (1997) reported a "slight advantage" of the bilingual condition relative to the monolingual condition in an adapted alternating treatments single case research design study with a child with language impairment. No signs of an inhibitory effect of bilingual instruction on English performance were reported in this study or in a similar study conducted with children with ASD who were bilingual (Summers, Smith, Mueller, Alexander, & Muzza, 2017). It is unknown the degree to which the findings from children with typical hearing apply to children with hearing loss, and more specifically to children with hearing loss who are bilingual.…”
Section: Direct Comparisons Of Bilingual and Monolingual Instructioncontrasting
confidence: 72%
“…Thordardottir, Weismer, and Smith (1997) reported a "slight advantage" of the bilingual condition relative to the monolingual condition in an adapted alternating treatments single case research design study with a child with language impairment. No signs of an inhibitory effect of bilingual instruction on English performance were reported in this study or in a similar study conducted with children with ASD who were bilingual (Summers, Smith, Mueller, Alexander, & Muzza, 2017). It is unknown the degree to which the findings from children with typical hearing apply to children with hearing loss, and more specifically to children with hearing loss who are bilingual.…”
Section: Direct Comparisons Of Bilingual and Monolingual Instructioncontrasting
confidence: 72%
“…Among the 11 studies that included children who were DLLs who also had delays or disabilities, four studies (Gutiérrez-Clellen et al, 2012; Simon-Cereijido & Gutiérrez-Clellen, 2014; Spencer et al, 2019; Thordardottir et al, 1997) conducted assessments to identify children with delays or disabilities in the children’s home language, three studies conducted assessments in English (Spencer et al, 2013; Spencer & Slocum, 2010; Weddle et al, 2016), and one study conducted assessments in both languages (Restrepo et al, 2013). Three studies did not report the language used to conduct the assessment (Landry et al, 2019; McDaniel et al, 2019; Summers et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used an alternating treatments design to compare differences between delivery of intervention using bilingual instruction versus English instruction on children’s expressive language skills (McDaniel et al, 2019; Summers et al, 2017; Thordardottir et al, 1997). In two studies, no differences were found between delivering intervention using bilingual instruction alternating with English instruction on expressive vocabulary (McDaniel et al, 2019) or making requests (Summers et al, 2017). Thordardottir et al (1997) reported bilingual instruction was more effective than English instruction in teaching children to label home-related vocabulary.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations